2007
DOI: 10.1065/jss2007.04.224
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological assessment of the effects of glyphosate and chlorpyrifos in an Argentine soya field

Abstract: Discussion. The ecotoxicological effects of pesticides can be assessed by monitoring the status of communities in real ecosystems or through the use of laboratory toxicity tests. Litterbag field test showed no influence of the treatments on the organic matter breakdown, suggesting a scarce contribution of soil macrofauna. The bait-lamina test, however, seemed to be useful for detecting the effects of GLY and CPF treatments on the activity of the soil fauna. CPF failed to give significant differences with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(82 citation statements)
references
References 38 publications
5
70
2
5
Order By: Relevance
“…These results contrast with those reported previously for a soybean fi eld on a clay silty soil sprayed with chlorpyrifos (Casabé et al, 2007). Physical structure and chemistry of the soils have a strong infl uence on this functional endpoint, and could account for the observed differences.…”
Section: Resultscontrasting
confidence: 57%
See 3 more Smart Citations
“…These results contrast with those reported previously for a soybean fi eld on a clay silty soil sprayed with chlorpyrifos (Casabé et al, 2007). Physical structure and chemistry of the soils have a strong infl uence on this functional endpoint, and could account for the observed differences.…”
Section: Resultscontrasting
confidence: 57%
“…Few studies, however, showed effects on neutral red retention time in earthworms exposed to chlorpyrifos contaminated soils (Hodge et al, 2000;Casabé et al, 2007;Reinecke & Reinecke, 2007). Our results showed that the neutral red retention time was sensitive to the low chlorpyrifos concentrations present in soil, and may constitute an early indication of impending physiological damage in the earthworms.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…The study of coelomocytes in earthworms is relevant because these leukocytes, located around the intestinal tract, are particularly exposed to soil pollutants and are involved in the process of cell immunity [Dhainaut andScaps, 2001, Manerikar et al, 2008]. The comet assay applied to earthworms has been used in previous studies to investigate the genotoxicity of artificial or natural soils spiked with dioxins [Verschaeve et al, 1993], heavy metals [Bierkens et al, 1998;Reinecke and Reinecke, 2004;Zhu et al, 2006;Manerikar et al, 2008], pesticides [Zang et al, 2000;Bustos-Obregón and Goicochea, 2003;Xiao et al, 2006a;Casabé et al, 2007], or PAHs [Martin et al, 2005;Zhu et al, 2006]. Yet, studies dealing with the genotoxicity of field-contaminated soils to earthworms are rare [White and Claxton, 2004].…”
Section: Introductionmentioning
confidence: 99%